2011
DOI: 10.1097/nrl.0b013e318218030a
|View full text |Cite
|
Sign up to set email alerts
|

Internal Carotid Artery Dissection Heralded by an Oculomotor Nerve Palsy

Abstract: Acute oculomotor nerve palsies with pupillary involvement warrant thorough investigation. When routine work-up fails to elucidate an etiology, extracranial carotid pathology should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Further, magnetic resonance imaging findings postoperatively did not demonstrate any midbrain stroke to explain the patient's examination findings [Figure 4b and c ]. Finally, the clinical course after discovery of the pupil is certainly compatible with previous reports of ICA dissection-associated third nerve palsy[ 8 ] or ischemic injury from perforator loss in the recanalized PCA. Our hypothesis, therefore, is that the most likely cause of third nerve palsy in this case was the recanalization of the fetal PCA.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Further, magnetic resonance imaging findings postoperatively did not demonstrate any midbrain stroke to explain the patient's examination findings [Figure 4b and c ]. Finally, the clinical course after discovery of the pupil is certainly compatible with previous reports of ICA dissection-associated third nerve palsy[ 8 ] or ischemic injury from perforator loss in the recanalized PCA. Our hypothesis, therefore, is that the most likely cause of third nerve palsy in this case was the recanalization of the fetal PCA.…”
Section: Discussionsupporting
confidence: 87%
“…[ 6 10 ] In a recent case report and review, Nizam et al . [ 8 ] summarized 16 cases of partial or complete third nerve involvement, along with other symptoms, in the setting of carotid artery dissection that have been reported in the literature. Interestingly, a fetal PCA variant would allow for additional proximal involvement of the nerve as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campos et al 6 described a case of a 50-year-old man who began having an occipital headache and developed diplopia days later, with objective impairment in right eye adduction and upward gaze and slight pupillary dilation with MR angiography evidence of a dissection of right extracranial ICA. Nizam et al 7 described a case of a 24-year-old man presenting a right hemianopsia, hemiparesis and hemihypestaesia 2 days after the onset of a right complete oculomotor nerve palsy, with MRI evidence of a dissection involving extracranial left ICAD and an acute infarct in left middle cerebral artery.
Learning points

Internal carotid artery dissection (ICAD) cases may present without the more common clinical signs, such as Horner syndrome, headache/neck pain or focal neurological ischaemic signs.

Although rare, cranial nerve palsies can be the only manifestation of an ICAD.

Considering the small group of patients presenting cranial nerve palsies in the setting of an ICAD, oculomotor nerve involvement is extremely rare.

The hypothesis of a cervicocerebral dissection should be considered when addressing a young patient with cranial nerve palsy.

…”
Section: Discussionmentioning
confidence: 99%
“…The spectrums of clinical presentations of ICA dissection included facial pain, neck pain, and concurrent HS in 4 patients; facial pain, HS, and contralateral sensorimotor deficit in 6; headache and contralateral sensorimotor deficit in 2; and contralateral sensorimotor deficit with or without speech impairment in 10. 93 Nizam et al 94 reported a left, pupil-involving oculomotor palsy as a rare presenting sign of left ICA dissection.…”
Section: Vascular Diseasementioning
confidence: 98%